Potential agricultural waste management modes to enhance carbon sequestration and aggregation in a clay soil - Israt Jahan Ami; Sonia Nasrin; Falguni Akter; Milton Halder (Waste Management Bulletin)
Agricultural wastes (crop residues) removal and burning, coupled with intensive farming, lead to soil quality degradation and carbon emissions. Agricultural wastes are considered an effective way to improve soil carbon stock and aggregation in soil. However, the suitable strategy for agricultural wastes management to enhance soil organic carbon stabilization and aggregation has not been intensively investigated. A short-term field study was conducted from 2021 to 2022 to assess the potential of agricultural wastes management approaches to enhance aggregation (MWD) and mineral-associated organic carbon. The study consisted of six treatments: (1) control, (2) fertilization (NPK), (3) agricultural waste burn and ash incorporation, (4) NPK + agricultural waste burn and ash incorporation, (5) agricultural waste application at 8 (rice) and 6 (okra) ton ha−1, and (6) NPK + agricultural waste application at 8 (rice) and 6 (okra) ton ha−1 with one year duration (Okra from mid-November to mid-March – fallow from mid-March to mid-July – lowland rice (Oryza sativa) mid-July to mid-November). Post-harvest soil aggregation, soil organic carbon (SOC), microbial biomass carbon (MBC), and glomalin-related soil protein (GRSP) were estimated. The findings exhibited that MWD (mm) under agricultural residue (0.49), residue + NPK (0.45), and only NPK (0.38) were enhanced compared to the control (0.28) (P < 0.05). The highest SOC (g kg−1) was found in residue + NPK (18.35), followed by only residue (18.10), and the lowest in the control (15) (P < 0.01). GRSP showed significant results, with the highest GRSP was observed with residue + NPK, followed by only residue application (p < 0.05). MBC and mineral-associated SOC of aggregates were reduced in the order of agricultural residue + NPK > agricultural residue > residue burn + NPK > NPK > residue burn > control. No significant results were found in terms of Fe oxides. Moreover, MWD was linked with SOC, while mineral-associated SOC was linked with MBC significantly. Results demonstrate that agricultural waste with NPK fertilizer has the potential to enhance aggregation, reduce erosion, and increase mineral-associated carbon in clay soil to mitigate climate change.